About Some Properties and Constructions of Experimental Designs - Ceranka, Bronisław; Graczyk, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
In this paper, we consider the problems related to the determining plan of the experiment performed according to the model of the chemical balance weighing design under additional assumption that the experimental errors are equally negatively correlated. This problem is studied from the point of view of D-optimality of such a design. We give new a construction method of D-optimal chemical balance weighing design and the list of possible experimental plans.